Can predatory mites aid in the management of the citrus leprosis mite? - Vechia, Jaqueline F. Della; Andrade, Daniel J.; Tassi, Aline D.; Roda, Amy; van Santen, Edzard; Carrillo, Daniel (Frontiers in Agronomy, 2023)
The flat mite Brevipalpus yothersi is the main vector of citrus leprosis in South and Central America and Mexico, where vector suppression using conventional acaricides is usually the only disease control method, leading to problems with acaricide resistance. This mite is present in Florida, where several viruses known to cause citrus leprosis were recently detected. This research builds preparedness for managing emerging viral diseases and mitigating potential problems associated with acaricide resistance by addressing the compatibility of chemical and biological control strategies against B. yothersi. The predatory mite Amblyseius largoensis has shown promise as a biological control agent of B. yothersi. However, the effects of acaricides used in citrus on this predator are unknown. This study investigated the impact of different routes of acaricide exposure on A. largoensis, including direct contact, pesticide-contaminated prey, residual contact, and combined exposure routes in laboratory settings. Additionally, the efficacy of A. largoensis in controlling B. yothersi, alone and in combination with acaricide applications, was evaluated under greenhouse conditions. Commonly used acaricides like abamectin and spirodiclofen were highly effective in controlling B. yothersi and only slightly harmful to A. largoensis. Other acaricides were also effective against B. yothersi but were less compatible with the predatory mite. In the greenhouse trial, all acaricides, alone or in combination with the predators, and the predators alone, effectively suppressed B. yothersi one month after treatment application. However, B. yothersi populations significantly increased one month later in the abamectin-alone and predator-alone treatments. At the same time, the combination of abamectin and predators provided B. yothersi suppression throughout the experiment. The fenpyroximatepredator combination also provided better control than each treatment applied independently. All other acaricides provided prolonged B. yothersi control, hindering biological control probably due to the lack of prey for A. largoensis. Research findings highlight the potential for enhancing the selectivity of acaricides towards A. largoensis by manipulating their exposure route. Combining predatory mites with acaricides shows promise in improving B. yothersi management.